2019
DOI: 10.1371/journal.pone.0222457
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of Mexican H7N3 highly pathogenic avian influenza viruses in poultry

Abstract: Highly pathogenic avian influenza (HPAI) virus subtype H7N3 has been circulating in poultry in Mexico since 2012 and vaccination has been used to control the disease. In this study, eight Mexican H7N3 HPAI viruses from 2015–2017 were isolated and fully sequenced. No evidence of reassortment was detected with other avian influenza (AI) viruses, but phylogenetic analyses show divergence of all eight gene segments into three genetic clusters by 2015, with 94.94 to 98.78 percent nucleotide homology of the HA genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The 2012 outbreak represented not only an animal health emergency but also a poultry production crisis, resulting in the death of over 22 million birds (either infected or culled), and an economic impact estimated at USD 720 million [30,33]. This H7N3 subtype has been circulating in poultry in Mexico since its first detection, causing repeated outbreaks both in commercial chickens and in backyard poultry [33][34][35][36]. Moreover, it has been suggested that Mexico could play a potential role as a hotspot for viral interchange, as it is located along various winter migration routes of wild birds [31].…”
Section: Introductionmentioning
confidence: 99%
“…The 2012 outbreak represented not only an animal health emergency but also a poultry production crisis, resulting in the death of over 22 million birds (either infected or culled), and an economic impact estimated at USD 720 million [30,33]. This H7N3 subtype has been circulating in poultry in Mexico since its first detection, causing repeated outbreaks both in commercial chickens and in backyard poultry [33][34][35][36]. Moreover, it has been suggested that Mexico could play a potential role as a hotspot for viral interchange, as it is located along various winter migration routes of wild birds [31].…”
Section: Introductionmentioning
confidence: 99%
“…The first outbreak of HPAIV caused by subtype H7N3 appeared in Pakistan in 1995 and affected 3.2 million birds, primarily breeders and boilers. Since then, it has caused outbreak in Chile (2004) [ 63 ], the Netherlands (2003) [ 64 ], British Colombia (2004) [ 65 ], and Mexico (2012) [ 66 ], causing heavy losses in the poultry industry. Although Kim et al reported the first isolations of two H7N3 strains during their 2008–2011 systemic surveillance program [ 13 ] in the Korean peninsula, detailed molecular and pathological studies from South Korea are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…This sequence analysis data might support the idea that the position 105 in NP may be a determinant for host adaptation or/and increased pathogenicity. Youk et al [ 39 ] demonstrated that the Mexican H7N3 HPAI viruses, after circulating in chicken populations for several years, retained high pathogenicity to chickens but decreased fitness in mallards. Some of the changes observed in the viral genomes of Mexican H7N3 between 2012 and 2016 were associated with a point mutation at A125T in HA, NP M105V, and NP S377N [ 39 ].…”
Section: Discussionmentioning
confidence: 99%